2022
DOI: 10.1007/s43032-022-01030-w
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Alanine Aminotransferase and Other Biochemical Parameters in Lean PCOS

Abstract: To explore the associations of alanine aminotransferase in lean women of polycystic ovary syndrome (PCOS) with other biochemical parameters and the potential risk factors. This is a retrospective cohort study with lean PCOS (n = 91) and healthy controls (n = 45); we reviewed the electrical records and databases of the PCOS patients in our infertility clinic between January 2019 and September 2021; independent t-test, linear correlation analysis, and multiple linear regression were used to explore the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…The results of liver enzymes activities were identical with other study [44], which they indicated a greater activity of ALT in PCOS patients, ascribed mostly to growing prevalence of obesity, hyperandrogenism, insulin resistance, and dyslipidemia associated with PCOS. Nevertheless, association in ALT and PCOS with obese situation had been documented more often compared to overweight PCOS.…”
Section: Discussionsupporting
confidence: 87%
“…The results of liver enzymes activities were identical with other study [44], which they indicated a greater activity of ALT in PCOS patients, ascribed mostly to growing prevalence of obesity, hyperandrogenism, insulin resistance, and dyslipidemia associated with PCOS. Nevertheless, association in ALT and PCOS with obese situation had been documented more often compared to overweight PCOS.…”
Section: Discussionsupporting
confidence: 87%
“…There were no differences in blood concentrations of estradiol, FSH, 17-OH progesterone and androstenedione. Higher levels of luteinizing hormone and total testosterone, were also confirmed in another study, but the authors did not take into account the division into phenotypes, but only into normal and excessive body mass [25]. .…”
Section: Resultsmentioning
confidence: 82%
“…Other authors also point to the occurrence of disturbances in biochemical parameters. However, it is important to remember about other factors influencing the differences in results, such as the body mass of the study group, the presence of fatty liver or the division into phenotypes [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence of high ALT levels in lean PCOS patients 42 . Our study suggests that ALT levels in PCOS may be linked to insulin resistance, irrespective of obesity.…”
Section: Discussionmentioning
confidence: 99%